Hollow silica nanospheres coated with insoluble calcium salts for pH-responsive sustained release of anticancer drugs. Issue 70 (9th August 2016) - Guo, Yuming; Fang, Qilong; Li, Han; Shi, Weike; Zhang, Jie; Feng, Jing; Jia, Weili; Yang, Lin
Abstract : Hollow silica nanospheres coated with pH-sensitive insoluble calcium salts are prepared for pH-responsive sustained release of anticancer drugs. Abstract : Hollow silica nanospheres coated with biocompatible and pH-sensitive inorganic insoluble calcium salts including calcium carbonate and hydroxyapatite have been successfully prepared. The results indicate that the nanospheres can efficiently load doxorubicin and release it in a pH-responsive and sustained manner, and improve the treatment efficacy significantly.